1999
DOI: 10.1002/1529-0131(199904)42:4<799::aid-anr25>3.3.co;2-w
|View full text |Cite
|
Sign up to set email alerts
|

Elevated parathyroid hormone 44–68 and osteoarticular changes in patients with genetic hemochromatosis

Abstract: Objective. To determine whether the osteoarticular changes associated with genetic hemochromatosis could be explained by metabolic parathyroid hormone (PTH) disorders.Methods. The study involved 210 patients with liver iron overload syndromes. Osteoarticular changes were numerically scored as the number of damaged joints. PTH 1-84 and 44-68 were assayed.Results. An increase in serum PTH 44-68 levels was found in one-third of untreated patients who had no calcium or PTH 1-84 abnormalities. Serum PTH 44-68 level… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
10
0

Year Published

1999
1999
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 14 publications
1
10
0
Order By: Relevance
“…The proportions of homozygotes (C282Y/C282Y) and compound heterozygotes (C282Y/H63D) were 87% and 13%, respectively, similar to proportions reported in 2 large observational studies that specifically assessed articular complications of HH 11,12 .…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…The proportions of homozygotes (C282Y/C282Y) and compound heterozygotes (C282Y/H63D) were 87% and 13%, respectively, similar to proportions reported in 2 large observational studies that specifically assessed articular complications of HH 11,12 .…”
Section: Discussionsupporting
confidence: 78%
“…Schumacher was the first to describe articular complications in patients with HH 9 . Since then, numerous observational studies have reported that affected individuals frequently show arthralgia in the hands and large joints or severe arthropathy, typically involving the second and third metacarpophalangeal (MCP) joints, which may seriously affect quality of life 4,5,10,11,12,13 . This arthropathy was reported to occur in 30% to 80% of patients with HH, depending on the study 5,14 , and frequently coexists with calcium pyrophosphate deposition 12 .…”
mentioning
confidence: 99%
“…One hospital case-control study found no significant association (OR=1.04, 95% CI 0.42 to 2.60), although patients with haemochromatosis developed CPPD at a younger age (<60) than those without haemochromatosis (OR=3.05, 95% CI 1.12 to 8.33) 67. In a study of 178 patients with untreated haemochromatosis (mean age 50 years) prevalence of CC was 30% and the number of joints with CC correlated positively with age, ferritin level and serum parathyroid hormone 44–68 pg/ml 70. In another hospital series of 54 patients with idiopathic haemochromatosis, (mean age 56, range 39–74 years), 31 (57%) had arthropathy which significantly associated with CC (OR=6.81, 95% CI 2.02 to 22.95)71.…”
Section: Resultsmentioning
confidence: 99%
“…Some studies found no relationship between C282Y and self-reported arthropathy,18 inflamed joints,19 chondrocalcinosis20 21 or subchondral arthritis 20. Other studies reported a significant association between C282Y and chondrocalcinosis,22 or late-onset hand osteoarthritis 21.…”
mentioning
confidence: 99%
“…Other studies reported a significant association between C282Y and chondrocalcinosis,22 or late-onset hand osteoarthritis 21. Few studies have addressed the role of H63D 20 21. Most studies on the HFE gene variants were based on clinical samples, and were prone to selection bias 23.…”
mentioning
confidence: 99%